2003
DOI: 10.1046/j.1365-2036.2003.01432.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclo‐oxygenase‐2 expression in Barrett's oesophageal carcinogenesis: an immunohistochemical study

Abstract: SUMMARYBackground: The incidence of Barrett's oesophageal adenocarcinoma is increasing more rapidly than any other malignancy in industrialized countries. Cyclooxygenase-2 appears to play an important role in gastrointestinal carcinogenesis. Previous studies on cyclo-oxygenase-2 expression in Barrett's oesophageal carcinogenesis have utilized tissue samples obtained from different patients. We sought a definitive comparison of cyclo-oxygenase-2 expression in the sequence of Barrett's metaplasia-dysplasia-adeno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 40 publications
1
22
0
Order By: Relevance
“…Considerable data have implicated COX-2 in BO and OAC: COX-2 expression increases in BO with the development of dysplasia and cancer (Cheong et al 2003), COX-2 inhibitors reduce proliferation and induce apoptosis in OAC cell lines in culture (Buttar et al 2002a) and COX-2 inhibitors reduce progression in animal models of BO (Buttar et al 2002b). However, the expression of COX-2 and prevention of disease by COX-2 inhibitors are not universal and factors such as G-Gly driving the avoidance of apoptosis by alternative pathways could contribute to progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Considerable data have implicated COX-2 in BO and OAC: COX-2 expression increases in BO with the development of dysplasia and cancer (Cheong et al 2003), COX-2 inhibitors reduce proliferation and induce apoptosis in OAC cell lines in culture (Buttar et al 2002a) and COX-2 inhibitors reduce progression in animal models of BO (Buttar et al 2002b). However, the expression of COX-2 and prevention of disease by COX-2 inhibitors are not universal and factors such as G-Gly driving the avoidance of apoptosis by alternative pathways could contribute to progression of cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Of these, doctors refused contact with 71 patients and 167 died before consent could be obtained. Patients who were too ill (91), were mentally incapable (23), could not read or write in English (41), or could not be contacted (26) were excluded. The remaining 1,191 patients were invited to participate, and, of these, 928 (78% of those approached) agreed to take part.…”
Section: Methodsmentioning
confidence: 99%
“…This class of medications inhibits the activity of the cyclooxygenase (COX) enzymes (both constitutional COX-1 and inducible COX-2 isoenzymes). COX-2 is overexpressed in many epithelial cancers, including esophageal cancers (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). With regard to tumor growth, COX-2 enzyme functions to reduce cellular adhesion and apoptosis and increase angiogenesis (38)(39)(40).…”
Section: Introductionmentioning
confidence: 99%
“…Experimentally statins inhibit proliferation and induce apoptosis in Barrett's cell lines and these effects are enhanced in an additive manner in combination with inhibition of the cyclo-oxygenase-2 pathway (10,11). Over-expression of COX-2 in Barrett's mucosa has been reported, and experimentally (34), and in clinical studies beneficial effects of COX-inhibitors on progression to cancer have been reported (13,16,(35)(36)(37). Thus it is possible that statin and aspirin impair survival of the Barrett's clone at a very early stage and so impair establishment of a mature Barrett's segment.…”
Section: Discussionmentioning
confidence: 99%